Relationship between managing risk, managing finance and networking towards Sarawak Bumiputera entrepreneur / Hairul Azlan Abd Aziz - Abd Aziz, Hairul Azlan (2016)
The purpose of this research is to describe the factors that influencing the success of Sarawak Bumiputera Entrepreneur business. Some of the Bumiputera entrepreneur in Sarawak have a good business skills and knowledge. Most of them able to sustain their business for a long time period since they had success in business. Thus, the study about relationship between managing risk, managing finance and networking towards Sarawak bumiputera entrepreneur is very important. By refers to previous journal and article, quantitative method was used in this research to examine managing risk, managing finance and networking. A cross-sectional survey was conducted in this research in order to distribute questionnaire to 200 of bumiputera entrepreneur in Kuching, Sarawak. To determine the impact and the relationship between independent and dependent variables, multiple regression and correlation analysis has been used. In the end of this study, networking was found as critical or important factor that led to success of bumiputera entrepreneur business in Kuching, Sarawak.